Arbitrage pricing theory and influences of macroeconomic factors in Malaysian capital market / Karunagaran A/L Madhavan and Deviga A/P Vengedasalam - Madhavan, Karunagaran A/L; Vengedasalam, Deviga A/P (2002)
This study was done to examine the influences of macroeconomics factors in determining the stock market return. Monthly closing price of 100 common stocks (stocks which are listed under the Kuala Lumpur Composite Index) were taken for the period of January 1997 to December 2001. Six macroeconomics variables were selected for this study based on some prior research. Variables are Money Supply, Trade volume, Interest Rate, Inflation Rate, Industrial Production Index and Composite Index. Data analysis was done by using Microsoft Excel and Statistical Package for Social Science (SPSS).